ANALYSIS OF CULTURAL WORDS IN THE ISLAMIC SELF-HELP BOOK BY YASMIN MOGAHED - frihatmawati, rizky; Yasin, Achmad; Rentiana, Leny Hikmah; Dhini, Ulfa Rahma (SIGEH ELT : Journal of Literature and Linguistics, 2025)
This study analyzes types of cultural words and translation procedures in the Islamic self-help book 'Reclaim Your Heart' by Yasmin Mogahed. The objectives of this study are to identify the cultural words in the book and the types of translation procedures applied in translating those words using a qualitative method. From the study's findings and discussion, it can be concluded that four basic categories of cultural words are present in the book: organization, material, gestures and habits, ecology, and social culture. The type of cultural word mostly found is organization related to the Islamic religion. From 57 samples of cultural words, 34 (59,6%) cultural words were categorized into organization, 7 (12,2%) cultural words were categorized into material culture, 6 (10,5%) cultural words were categorized into gesture and habit, 5 (8,7%) cultural words were categorized into ecology and the rest were five cultural words that belonged to social culture (8,7%). In translating cultural words, the study reveals that the translator employed transference, naturalization, literal translation, explanation, and adaptation procedures